Evaluation of the effects of COVID‐19 pandemic on hair diseases through a web‐based questionnaire. Issue 6 (16th July 2020) - Turkmen, Dursun; Altunisik, Nihal; Sener, Serpil; Colak, Cemil
Abstract: Aim: Current quarantine conditions are a difficult process for individuals and can worsen the psychological state. Increased psychosocial stress can affect the course of many common "stress‐sensitive" skin conditions. This study examined the possible effects of coronavirus disease 2019 (COVID‐19) on hair and scalp diseases such as telogen effluvium (TE), alopecia areata (AA), and seborrheic dermatitis (SD) in individuals who had to stay at home for a long time and the patients' methods of dealing with these diseases. Methods: The study was conducted using an online questionnaire. All the individuals were asked questions about pre‐ and post‐pandemic TE, AA, and SD. Participants with complaints were asked what they did for treatment. Results: During the pandemic, TE was seen in 27.9% of the participants, AA on the scalp was seen in 2.8%, AA on the face was seen in 2.5%, and SD was seen in 19.9%. Applying to a dermatologist for complaints during the pandemic was lower than before pandemic. TE was higher in women before and during the pandemic. Conclusion: It was found that the rates of referring to a dermatologist for the complaints before the pandemic varied between 15% and 28% and that these rates decreased significantly during the pandemic (2.5%‐12.5%).